2012
DOI: 10.1111/j.1462-5822.2012.01764.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Trypanosoma cruzi persistence in Chagas disease

Abstract: Summary Trypanosoma cruzi infection leads to development of chronic Chagas disease. In this article, we provide an update on the current knowledge of the mechanisms employed by the parasite to gain entry into the host cells and establish persistent infection despite activation of a potent immune response by the host. Recent studies point to a number of T. cruzi molecules that interact with host cell receptors to promote parasite invasion of the diverse host cells. T. cruzi expresses an antioxidant system and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
111
0
13

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 142 publications
(127 citation statements)
references
References 60 publications
(69 reference statements)
3
111
0
13
Order By: Relevance
“…However, the presence of blood trypomastigotes or parasite DNA in cardiac tissue from some animals treated with this combination was still detected after immunosuppression, hemocultures, or PCR. Previous studies showed that although early treatment with Bz is effective at eliminating parasitemia, parasitological cure is not always achieved due to the presence of T. cruzi reservoirs resistant to chemotherapy, which are distributed throughout multiple organs and tissues (35,36). Thus, there is evidence that the efficiency of etiological treatment is directly influenced by multiple factors, especially the variable profiles of resistance to infection observed in different mouse strains (28,37), parasite virulence, and the different sensitivities of T. cruzi strains to Bz (9,38).…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of blood trypomastigotes or parasite DNA in cardiac tissue from some animals treated with this combination was still detected after immunosuppression, hemocultures, or PCR. Previous studies showed that although early treatment with Bz is effective at eliminating parasitemia, parasitological cure is not always achieved due to the presence of T. cruzi reservoirs resistant to chemotherapy, which are distributed throughout multiple organs and tissues (35,36). Thus, there is evidence that the efficiency of etiological treatment is directly influenced by multiple factors, especially the variable profiles of resistance to infection observed in different mouse strains (28,37), parasite virulence, and the different sensitivities of T. cruzi strains to Bz (9,38).…”
Section: Discussionmentioning
confidence: 99%
“…The establishment of a long-term infection in the heart and the development of a cardiomyopathy condition are directly related to the ability of T. cruzi to infect and persist within cardiomyocytes during the acute phase of infection [33,34] . Cardiomyocytes are differentiated cells that respond to T.cruzi infection by initiating adaptive strategies.…”
Section: Tcruzimentioning
confidence: 99%
“…In this sense, the infection and persistence by protozoan parasites is associated with changes in host tissue protein composition, highlighting that both parasite and host-derived molecules modulate disease progression [113,115]. For instance, these kind of bidirectional protein signatures have been identified by proteomics in Plasmodium falciparum [116].…”
Section: The Potential Of Biosensors To Detect and Diagnose Parasitesmentioning
confidence: 99%